2015
DOI: 10.1111/ijfs.12935
|View full text |Cite
|
Sign up to set email alerts
|

Composition and functionality of wheat bran and its application in some cereal food products

Abstract: SummaryProduction of wheat bran (WB) for human consumption is estimated to be about 90 million tonnes per year. WB is a cheap and abundant source of dietary fibre which has been linked to improved bowel health and possible prevention of some diseases such as colon cancer. It also contains minerals, vitamins and bioactive compounds such as phenolic acids, arabinoxylans, alkylresorcinol and phytosterols. These compounds have been suggested as an aid in prevention of noncommunicable diseases such as cardiovascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
195
1
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 313 publications
(208 citation statements)
references
References 54 publications
(105 reference statements)
6
195
1
6
Order By: Relevance
“…Wheat bran (WB) is an essential by-product of wheat during the milling process, and contains about 45-53% dietary fibre (Majzoobi et al, 2012;Dnipe et al, 2015). Several health benefits have been accrued to consumption of WB-enriched or whole wheat foods such as improved gut health, reduced risk of colon cancer and cardiovascular diseases; and these benefits are linked to minerals, vitamins and other phytochemicals that are present in the bran fraction of wheat (Dnipe et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wheat bran (WB) is an essential by-product of wheat during the milling process, and contains about 45-53% dietary fibre (Majzoobi et al, 2012;Dnipe et al, 2015). Several health benefits have been accrued to consumption of WB-enriched or whole wheat foods such as improved gut health, reduced risk of colon cancer and cardiovascular diseases; and these benefits are linked to minerals, vitamins and other phytochemicals that are present in the bran fraction of wheat (Dnipe et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Several health benefits have been accrued to consumption of WB-enriched or whole wheat foods such as improved gut health, reduced risk of colon cancer and cardiovascular diseases; and these benefits are linked to minerals, vitamins and other phytochemicals that are present in the bran fraction of wheat (Dnipe et al, 2015). Although WB has mainly been used as animal feed supplements its use as human food is still less than expected because of its unfavourable impact on functional and sensory properties (Kock et al, 1999;Zhang & Moore, 1999;Song et al, 2013;Hemdane et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…They have the capability of complexing heavy metal ions which facilitate their removal by adsorption. The processing of agro-waste for their modification into carbon form is needed as in this form the agro-waste possesses high porosity and large surface area making it more effective for metal adsorption process [14,38].…”
Section: Pulse Milling Wastementioning
confidence: 99%
“…WB is composed of about 53 % dietary fibre (xylans, lignin, cellulose, galactan, and fructans). Other components include vitamins and minerals and bioactive compounds such as alkylresorcinols, ferulic acid, flavonoids, carotenoids, lignans and sterols (Onipe et al, 2015). In the last decades, several studies have shown potential in incorporation of WB in cereal based products such as bread (Nandeesh et al, 2011;Boita et al, 2016;Le Bleis et al, 2015), biscuits, cookies (Silky et al, 2014;Kamal 2015;Ellouze-Ghorbel et al, 2010) and cakes (Lebesi and Tzia, 2011).…”
Section: Introductionmentioning
confidence: 99%